Do Relationship- and Self-Oriented Deceptions Impact the Effect of Attitude Alignment on Attraction?. Issue 5 (17th June 2021) - Reid, Chelsea A.; Shoemaker, Hannah L.; Wallace, Delaney M.
Abstract: While individuals value honesty in relationships, disagreements can create discomfort and individuals tend to prefer partners who engage in attitude alignment (i.e., shift their attitude toward agreement when disagreement occurs). In order to maintain smooth interactions, partners may even deceive individuals by concealing their continued disagreement. In a 2 (Attitude Alignment Deception) x 2 (Partner Motivation) between-subjects design, we examined whether individuals would evaluate interaction partners who engaged in deceptive attitude alignment less favorably compared to interaction partners who engaged in honest attitude alignment, and we examined whether partner motivation (relationship- vs. self-oriented) impacted this effect. After a brief in-person discussion about a disagreed upon social issue, participants received written feedback, allegedly from their interaction partners, that their partners engaged in attitude alignment that was either honest (i.e., partner came to agree with the individual) or deceptive (i.e., partner pretended to reach agreement with the individual). Participants also received feedback that their partners actions were motivated by either a relationship-orientation (i.e., to be liked by the individual) or self-orientation (i.e., to be viewed as correct on the issue). Individuals evaluated (e.g., were less attracted to) partners who engaged in deceptive (vs. honest) attitude alignment less favorably, but deceptive partners were evaluated more favorably if their deception was relationship- vs. self-oriented.